Psychologic Distress and Quality of Life After ICU Treatment for Coronavirus Disease 2019: A Multicenter, Observational Cohort Study. (10th August 2021) - Vlake, Johan H.; Van Bommel, Jasper; Hellemons, Merel E.; Wils, Evert-Jan; Bienvenu, O. Joseph; Schut, Anna F. C.; Klijn, Eva; Van Bavel, Marten P.; Gommers, Diederik; Van Genderen, Michel E.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To quantify short- and long-term psychologic distress, that is, symptoms of posttraumatic stress disorder, anxiety, and depression, and the health-related quality of life in coronavirus disease 2019 ICU survivors. DESIGN: A prospective, observational cohort study. SETTING: Postcoronavirus disease 2019 clinics of three hospitals in Rotterdam, the Netherlands. PATIENTS: Adult patients admitted for coronavirus disease 2019 to the ICU, who visited the postcoronavirus disease 2019 follow-up clinic. MEASURES AND MAIN RESULTS: The primary outcomes were psychologic distress and overall and mental health-related quality of life, assessed using the Impact of Event Scale-Revised, Hospital Anxiety and Depression Scale, Short-Form 36, and European Quality of Life 5D, 6 weeks, 3 months, and 6 months post hospital discharge. Second, we compared 3-month psychologic and mental health-related quality of life outcomes with a historical critical illness survivor cohort and overall and mental health-related quality of life with the Dutch population. We included 118 patients with a median age of 61 years (95% range, 36–77 yr) of whom 79 (68%) were male. At 6 weeks, 13 patients (23%) reported psychologic distress, copresence of probable psychiatric disorders was common, and no decline in psychologic distress was observed throughout follow-up. Coronavirus disease 2019 patients tend to suffer less from posttraumatic stress disorder and reported less severe symptoms of anxiety (Hospital Anxiety and Depression Scale Anxiety Score: 3 [0–17] vs 5 [0–16]; estimated mean difference 2.3 [95% CI, 0.0–4.7]; p = 0.05) and depression (Hospital Anxiety and Depression Scale Depression Score: 3 [0–15] vs 5 [0–16]; estimated mean difference 2.4 [95% CI, 0.1–2.4]; p = 0.04) than the historical critical illness cohort. Overall and mental health-related quality of life increased over time. Coronavirus disease 2019 ICU survivors reported better mental health-related quality of life than our historical cohort, but overall and mental health-related quality of life was still poorer than the Dutch population. CONCLUSIONS: Psychologic distress was common in coronavirus disease 2019 ICU survivors and remained similar until 6 months after hospital discharge. Health-related quality of life increased over time and was higher than in a historical cohort, but was lower than in the Dutch population. Our findings highlight that coronavirus disease 2019 ICU survivors should be monitored after ICU treatment to detect possible psychologic distress.